DIGITIZING BUSINESS PROCESSES TO IMPROVE OPERATIONAL EFFICIENCY IN COMPANIES - Abdul Hakim Satria Nusantara; Achmad Taufiq Kartaatmadja; Irhan Khairul Umam; RD. Rokhmad Saedudin (RAM PUBLISHER, 2024)
Digitalization has a role in improving company performance. Companies can form an organizational (company) work culture and provide competency improvement programs to increase employee productivity and performance so that they are able to make a positive contribution to improving company performance. Leadership roles in companies play an important role in improving company performance through providing motivation, providing basic needs and rewarding (recognition) employees. Digitalization also has a positive impact in carrying out company control regarding production performance or output, administering HR management digitally, business processes can be faster and more integrated. The application of digitalization provides a better experience in more accurate reporting, thereby being able to encourage business growth.